Efficacy and acceptance of a high‐velocity microdroplet device for interdental cleaning in gingivitis patients—A monitored, randomized controlled trial. Issue 2 (24th May 2017) - Stauff, I; Derman, SHM; Barbe, AG; Hoefer, KC; Bizhang, M; Zimmer, S; Noack, MJ
Abstract: Objectives: To compare in a randomized clinical trial the efficacy of a high‐velocity microdroplet device for interdental cleaning vs dental floss at reducing plaque and gingivitis. Methods: Sixty participants with an irregular interdental home cleaning regime were randomly assigned to use either a microdroplet device (n=40, test) or dental floss (n=20, control) for 4 weeks. At baseline and reassessment, the papilla bleeding index, the modified proximal plaque index and the amount of gingival crevicular fluid (GCF) were recorded. At the second appointment, participants completed a questionnaire regarding their assigned interdental cleaning option. The process quality of this investigator‐initiated trial was ensured by independent scientific observers and media representatives. Results: Improvement in the interdental cleaning routine reduced gingivitis in both groups ( P <.05). The microdroplet device was more effective at reducing plaque ( P =.003). The GCF amount remained the same in both groups. Comfort of use was greater with the microdroplet device. However, self‐reported effectiveness was superior with dental floss. About 85% of participants using the microdroplet device said they would continue daily use. Conclusion: Improving the interdental cleaning routine with the microdroplet device or dental floss reduced gingivitis and plaque in both groups. Acceptance regarding comfort of use was higher with the microdroplet device. Dental floss remained the first choice for narrow interdental spaces, yet the microdroplet device offers an effective and well‐accepted alternative for patients who fail the proper flossing routine.